Given x+1/x=2cosy then find x^n +1/x^n, Mathematics

Here we know x can only be 1 or -1. so if it is 1 ans is 2.

if x is -1, for n even ans will be 2

if x is -1 and n is odd ans will ne -2.

so we can see evenfor negative x also ans is 2 while sgn you were using would give ans -2 so you can see 2 sgn(x) is wrong.

so ans will be 2 ecxept when x is -1 and n is odd then it will be -2.

Posted Date: 3/12/2013 12:56:14 AM | Location : United States







Related Discussions:- Given x+1/x=2cosy then find x^n +1/x^n, Assignment Help, Ask Question on Given x+1/x=2cosy then find x^n +1/x^n, Get Answer, Expert's Help, Given x+1/x=2cosy then find x^n +1/x^n Discussions

Write discussion on Given x+1/x=2cosy then find x^n +1/x^n
Your posts are moderated
Related Questions
Find the volume of a cylinder of radius r and height h. Solution : Here, as we mentioned before starting this illustration we actually don't require using an integral to get t

Find out the length of the parametric curve illustrated by the following parametric equations. x = 3sin (t) y = 3 cos (t) 0 ≤ t ≤ 2? Solution We make out that thi

|a.x|=1 where x = i-2j+2k then calculate a

Tori was asked to provide an example of the commutative property of addition. Which of the subsequent choices would be correct? Using the simple interest formula Interest = pr


#question Show that the enveloping cylinder of the conicoid ax 2 + by 2 + cz 2 = 1 with generators perpendicular to the z-axis meets the plane z = 0 in parabolas

If each interior angle of a regular polygon has a calculated as of 144 degrees, Determine the numbers of sides does it have? a. 8 b. 9 c. 10 d. 11   c. The measur

Three Dimensional Spaces In this section we will start taking a much more detailed look at 3-D space or R 3 ).  This is a major topic for mathematics as a good portion of Calc

Magnitude - Vector The magnitude, or length, of the vector v → = (a1, a2, a3) is given by, ||v → || = √(a 1 2 + a 2 2 + a 2 3 ) Example of Magnitude Illus

Which of the following sets are equal? S 1 = {1, 2, 2, 3}, S 2 = {x | x 2 - 2x + 1 = 0}, S 3 = {1, 2, 3}, S 4 = {x | x 3 - 6x